Perceived Skills and Training Needs Among Singaporean School Personnel in Using Functional Behavior Assessments and Behavioral Interventions. (November 2019) - Dutt, Anuradha S.; Chen, Iris; Nair, Rahul
The aim of this exploratory study was to investigate the level of skills and training needs reported by special educators and teaching associates in functional behavioral assessment (FBA) and behavioral interventions within special education (SPED) schools in Singapore. The Skills and Needs Inventories in Functional Behavior Assessments and Interventions (SNI-FBAI), a self-report inventory, was administered to 378 special educators and 38 teaching support staff across seven SPED schools in Singapore. Perceived ratings across both groups were obtained across 13 items for skills and six items for training needs in FBA and behavioral interventions. The results suggested that special educators and teaching associates indicated relatively lower ratings on their perceived skill in more items related to conducting an FBA when compared with items related to behavioral interventions. In terms of training needs, both groups rated developing skills in FBA and behavioral interventions for managing severe challenging behaviors as a priority area for training.